Current development of stretchable self-powered technology based on nanomaterials toward wearable biosensors in biomedical applications - Wang, Qianqian; Sun, Xu; Liu, Chen; Wang, Chunge; Zhao, Wenjie; Zhu, Zehui; Ma, Sainan; Zhang, Sheng (Frontiers in Bioengineering and Biotechnology, 2023)
Cooperating with the burgeoning artificial intelligence and Internet-of-things (IoT), the innovative tendency of the next-generation biosensing system is towards intellectualization, miniaturization, and wireless portability. Self-powered technology has captured enormous research efforts due to the traditional rigid and cumbersome power sources being gradually out of the match with the wearable biosensing system. The research progress of various stretchable self-powered strategies for wearable biosensors and the involved integrated sensing system has demonstrated their promising potential in practical biomedical applications. In this review, the up-to-date research advances of dominating energy harvest strategies are discussed, together with the future outlook and remaining challenges which shed light on the follow-up research priorities.